2015
DOI: 10.4236/jamp.2015.311171
|View full text |Cite
|
Sign up to set email alerts
|

Kadomstev-Petviashvilli-Burgers (KPB) Equation in a Five Component Cometary Plasma with Kappa Described Electrons and Ions

Abstract: We investigate the existence of Ion-Acoustic solitary/shock waves in a five component cometary plasma consisting of positively and negatively charged oxygen ions, kappa described hydrogen ions, hot electrons and cold electrons. The KPB equation is derived for the system; its solution is plotted for different kappa values, as well as for the temperature ratios of ions. It is found that the amplitude of solitary structure increases with increasing kappa values and negatively charged oxygen ion densities. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Shahmansouri [19] studied dissipative dust acoustic solitary waves in plasmas having superthermal ions, and it was concluded that with the superthermal ions approaching a critical value the polarity of the solitary wave changes. Michael et al [20] in a recent report discussed the effect of kappa distributed electrons and ions on shocks/solitons in a dissipative five-component plasma and came to the conclusion that the spectral index of the distribution of electrons and ions controls the transformation of the solitary wave into a shock wave for this type of plasma. Hossen et al [21] discussed the heavy ion acoustic solitary and shock waves in non-thermal adiabatic plasma and found a strong dependence of potential profiles of shock and solitary waves on different dissipative plasma parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Shahmansouri [19] studied dissipative dust acoustic solitary waves in plasmas having superthermal ions, and it was concluded that with the superthermal ions approaching a critical value the polarity of the solitary wave changes. Michael et al [20] in a recent report discussed the effect of kappa distributed electrons and ions on shocks/solitons in a dissipative five-component plasma and came to the conclusion that the spectral index of the distribution of electrons and ions controls the transformation of the solitary wave into a shock wave for this type of plasma. Hossen et al [21] discussed the heavy ion acoustic solitary and shock waves in non-thermal adiabatic plasma and found a strong dependence of potential profiles of shock and solitary waves on different dissipative plasma parameters.…”
Section: Introductionmentioning
confidence: 99%